2010
DOI: 10.1097/aud.0b013e3181bdbac0
|View full text |Cite
|
Sign up to set email alerts
|

Ocular and Cervical Vestibular-Evoked Myogenic Potentials: A Study To Determine Whether Air- or Bone-Conducted Stimuli Are Optimal

Abstract: Using BCV mode, Fz and inion may be the optimal sites for eliciting oVEMPs and cVEMPs, respectively. Thus, BCV mode can be substituted for ACS mode to elicit oVEMPs and cVEMPs in the future, especially in "mass detection." In contrast, ACS mode provides an essential clinical merit of site selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1
4

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 16 publications
7
51
1
4
Order By: Relevance
“…Compared to oVEMPs elicited in response to ACS, BCV oVEMPs show higher response prevalences and greater amplitudes in healthy subjects Wang et al, 2010). In subjects with conductive hearing loss, BCV oVEMPs are usually normal whereas ACS oVEMPs are affected.…”
Section: Stimulation Parametersmentioning
confidence: 99%
“…Compared to oVEMPs elicited in response to ACS, BCV oVEMPs show higher response prevalences and greater amplitudes in healthy subjects Wang et al, 2010). In subjects with conductive hearing loss, BCV oVEMPs are usually normal whereas ACS oVEMPs are affected.…”
Section: Stimulation Parametersmentioning
confidence: 99%
“…In the last decade, various ways of VEMP stimulation have been investigated, such as air-conducted (AC) sound, bone conducted (BC) sound and vibration and galvanic stimuli, both mono-and binaurally [Rosengren et al, 2005Chihara et al, 2007Chihara et al, , 2009bWelgampola, 2008;Welgampola et al, 2009;Wang et al, 2010]. It has been shown that AC sound is easy to use in a clinical setting and the stimulus characteristics can be controlled; for example, the duration, level and frequency of the stimulus can be easily changed.…”
Section: General Introduction To Vestibular Evoked Myogenic Potentialsmentioning
confidence: 99%
“…Consecutive runs were performed to confirm the reproducibility of the p13 and n23 peaks. At our laboratory, the norm of the p13 latency of BCV-cVEMPs is 14.4 ± 1.5 ms. Those with p13 latency exceeding 17.4 ms are defined as delayed response [14].…”
Section: Cvemp Testmentioning
confidence: 99%